Procedimientos contables en la elaboración de estados financieros de la Compañía de Transporte Escolar e Institucional Riveras del Babahoyo S.A. en el período 2019 - Arciniegas Gonzalez, Franklin Alexander (2020)
The Babahoyo Riveras del Babahoyo School and Institutional Transportation Company “CTEIRB” SA is located in the city of Babahoyo. The construction of the financial statements involves an entire accounting process that begins on January 1 and ends on December 31 of the respective fiscal period, in compliance with the regulations and laws that dictate the procedures that must be followed so that the information contained in the financial statements faithfully represent what happened in the accounting period and the financial situation of the company. However, many companies carry out accounting procedures empirically and not observing certain stages that must be fulfilled in order to perform them correctly, the reason for which the present investigation was carried outIt is to describe which accounting procedures should have been applied, using bibliographic concepts of authors that explain the stages that must be met in an accounting procedure and the way in which each one of them should be carried out. It is of great importance that companies are guided by the norms and laws since in this way they will have a clear and global concept of how to carry out the accounting procedures and that this does not represent an internal problem as well as non-conformities with the information exposed before the partners, as external with the control entities in the future. The type of methodology used in this research is descriptive and bibliographic and the problem was learned through an interview with the General Manager of the company.